ERRORS ON SUBJECT-VERB AGREEMENT MADE BY THIRD SEMESTER STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF NIAS RAYA UNIVERSITY - Senadaman Wau (Institut Pendidikan Tapanuli Selatan, 2024)
Subject and verb agreement is the grammatical rule that the subject and the verb used in a sentence match each other. The third semester students of English Language Education Study Program of Nias Raya University faced the problem in subject-verb agreement aspect. The objective of this research was investigating subject-verb agreement made by the third semester students of English Language Education of Nias Raya University with the number of students was 37 persons. The primary source of the data was the students’ papers in writing sentences. The errors made were determined by the rule of subject-verb agreement (Greenbaum & Nelson, 2002). The result of data analysis was the third semester students made the errors on subject–verb agreement used or linked by: -number and person, -and, -or, -neither…nor, -preposition: with, as well as, -collective nouns, -indefinite pronouns, -quantity phrases, -singular nouns ending in –s, -relative pronoun: who, that, -pronoun: what, -introductory there, -citation and titles. The result of this research is expected being significant for English lecturer to search for solution for this problem